Sputum eosinophilia in idiopathic pulmonary fibrosis. - Birring, S; Parker, D; McKenna, S; Hargadon, B; Brightling, C; Pavord, I; Bradding, P (2005)
OBJECTIVES AND DESIGN: Cough is a common symptom in idiopathic pulmonary fibrosis that is difficult to treat and has a major impact on quality of life. We tested the hypothesis that the cough and increased cough reflex sensitivity seen in patients with idiopathic pulmonary fibrosis may be due to airway inflammation in a prospective, cross-sectional study. SUBJECTS AND METHODS: We measured the induced sputum inflammatory cell profile and cell-free supernatant inflammatory mediator concentrations in 15 patients with idiopathic pulmonary fibrosis, 17 healthy controls and 15 patients with chronic obstructive pulmonary disease. RESULTS: Both the geometric mean sputum differential eosinophil cell count and median eosinophilic-cationic-protein concentration were significantly higher in patients with idiopathic pulmonary fibrosis than controls (2.1% vs 0.3%; p <0.001 and 1.1 mg/ml versus 0.2 mg/ml; p=0.03 respectively). There were no significant differences in sputum eosinophil counts and eosinophilic-cationic-protein concentrations between patients with idiopathic pulmonary fibrosis and chronic obstructive pulmonary disease. Sputum leukotriene-B4 concentrations were significantly lower in patients with idiopathic pulmonary fibrosis (p=0.03) and chronic obstructive pulmonary disease (p=0.008) compared to controls. CONCLUSIONS: Idiopathic pulmonary fibrosis is characterised by the presence of active eosinophilic airway inflammation raising the possibility that airway inflammation may contribute to symptoms such as cough.